Country material distribution and adolescents' perceived health: multilevel study of adolescents in 27 countries. Issue 2 (13th January 2006) - Torsheim, Torbjorn; Currie, Candace; Boyce, Will; Samdal, Oddrun
Abstract : Objective: To assess the impact of country material distribution on adolescents' perceptions of health. Design: Cross sectional multilevel study. Setting: Data were collected from the school based health behaviour in school aged children: WHO cross national study 1997/98, which includes students from 27 European and North American countries. Participants: 12 0381 students in year 6, 8, and 10 who were attending school classes on the day of data collection. Main result: Adolescents in countries with a high dispersion of family affluence were more likely to have self rated poor health even after controlling for individual family level of affluence and family social resources. Conclusion: There are substantial inequalities in subjective health across European and North American countries related to the distribution of family material resources in these countries.